Total alkalinity flux in coral reefs estimated from eddy covariance and sediment pore‐water profiles. (31st December 2014) - Yamamoto, Shoji; Kayanne, Hajime; Tokoro, Tatsuki; Kuwae, Tomohiro; Watanabe, Atsushi
Abstract Ocean acidification decreases the pH of seawater and the seawater saturation state with respect to CaCO3 minerals. In the event of ocean acidification, Mg‐calcite is considered to be the first mineral to dissolve. Dissolution of Mg‐calcite is more prevalent at depth in the sediment than at the sediment interface because of production of CO2 resulting from microbial decomposition of organic matter. Rates of CaCO3 dissolution can be estimated from total alkalinity (AT) fluxes calculated from concentration gradients and diffusion coefficients. We estimated AT flux in a sandy area of the Shiraho coral reef under natural hydrodynamic conditions using eddy covariance and sedimentary AT profiles. The calculated nighttime AT flux at the sediment–water interface was 0.4–2.6 mmol m−2 h−1. Analysis of the sedimentary profile at a depth of 0–20 mm indicated that respiration by organisms consumed oxygen and produced CO2 during night and that photosynthesis enhanced O2 concentrations during the day. However, dissolved oxygen was depleted at all times in sediments deeper than 20 mm. The pore‐water aragonite saturation state (=Ωa) was constant at ∼ 3.0, which is equivalent to a value of 1.0 for the saturation state with respect to foraminifera (=Ωfora), as determined in a previous study. Both organic reactions (e.g., respiration) and inorganic Mg‐calcite dissolution occur in the sediment, leading to a constant Ωfora value in the sediment. These data confirm the metastable equilibrium of pore water with respect to Mg‐calcite from foraminifera, which is the most soluble phase in the sediment.